A Case of Alport Syndrome with Posttransplant Antiglomerular Basement Membrane Disease despite Negative Antiglomerular Basement Membrane Antibodies by EIA Treated with Plasmapheresis and Intravenous Immunoglobulin. (2nd December 2013) - Armstead, Sumiko I.; Hellmark, Thomas; Wieslander, Jorgen; Zhou, Xin J.; Saxena, Ramesh; Rajora, Nilum
Abstract : Posttransplant antiglomerular basement membrane (anti-GBM) disease occurs in approximately 5% of Alport patients and usually ends in irreversible graft failure. Recent research has focused on characterizing the structure of the anti-GBM alloepitope. Here we present a case of a 22-year-old male with end-stage renal disease secondary to Alport syndrome, with a previously failed renal allograft, who received a second deceased-donor kidney transplant. Six days after transplantation, he developed acute kidney injury. The serum anti-GBM IgG was negative by enzyme immunoassay (EIA). On biopsy, he had crescentic glomerulonephritis with linear GBM fixation of IgG. With further analysis by western blotting, we were able to detect antibodies to an unidentified protein from the basement membrane. This patient was treated with plasmapheresis twice per week and monthly intravenous immunoglobulin (IVIG) for a total of five months. At the end of treatment, these unknown antibodies were no longer detected. His renal function improved, and he has not required dialysis. We conclude that anti-GBM disease in patients with Alport Syndrome may be caused by circulating antibodies to other components of the basement membrane that are undetectable by routine anti-GBM EIA and may respond to treatment with plasmapheresis and IVIG.